Geospatial-Based Information Systems Model for Disaster Management of Reproductive Health - Muhammad Sapoan Hadi; Sutanto Priyo Hastono; Kemal Nazarudin Siregar; Dumilah Ayuningtyas (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Indonesia is a disaster-prone area, but it is often found that the response process is slow at the very beginning of a disaster. Furthermore, disasters are often unpredictable. Therefore, simulation of preparedness, mitigation, and disaster management should be conducted continuously and systematically, both in manual and electronic manner by utilizing advance technology in geospatial. The aim of this study to develop a model of geospatial-based information systems in disaster management of reproductive health sub-cluster (SIGAB KESPRO BISA) in Nusa Tenggara Barat. Data collection was conducted through in-depth interviews with several stakeholders. To complete the methodological approach and to obtain the system requirement, a content analysis was done toward in-depth interviews result. The research continued with the development of information system models. The analysis results by in-depth interview indicate the availability of infrastructure and the importance of the system offered. The SIGAB KESPRO BISA model needs to be composed of three main functions, namely preparedness and mitigation systems, logistics distribution, and reproductive health services. The design of the SIGAB KESPRO BISA model has been built to facilitate the process of developing the SIGAB KESPRO BISA application system so that disaster management can be carried out with high effectiveness and efficiency.